A palaeogeographic context for Neoproterozoic glaciation - Hoffman, P.; Li, Zheng-Xiang (Elsevier Science BV, 2009)
The distributions of 77 Neoproterozoic glacigenic formations are shown on global palaeogeographic maps for 715 Ma (Sturtian), 635 Ma (Marinoan) and 580 Ma (Ediacaran), constructed on grounds independent of palaeoclimatic indicators. The meridional distribution of Sturtian and Marinoan deposits is biased in favour of low palaeolatitudes, whereas Ediacaran deposits are biased in favour of high palaeolatitudes. All carbonate hosted glacigenic formations (n=22) fall within 35 of the palaeoequator. Most (6 of 8) examples of periglacial polygonal sand-wedges occur at palaeolatitudes greater than 30, whereas most (8 of 9) occurrences of large syn-glacial Fe and Fe-Mn deposits lie within 30 of the palaeoequator. Marinoan syndeglacial cap dolostones (n=24) decline in maximum thickness with palaeolatitude, consistent with poleward ice retreat, normal meridional temperature gradients and a small-obliquity orbit. Meridional (N-S) mean orientations of giant wave ripples in Marinoan cap dolostones from different regions (n=10) and absence of zonal (W-E) orientations are consistent with zonal wind-driven waves and not with hurricanes. In general, the results support the validity of the palaeogeographic reconstructions and the pan-glacial character of Sturtian and Marinoan ice ages.